KEPADATAN DAN POLA PENYEBARAN Shorea leprosula Miq. DI STASIUN PENELITIAN CABANG PANTI TAMAN NASIONAL GUNUNG PALUNG KALIMANTAN BARAT - Sholihin, Nur; Wardoyo, Elvi Rusmiyanto Pancaning; Rafdinal, Rafdinal (Universitas Tanjungpura, 2020)
Shorea leprosula has high economic and ecological value. Shorea leprosula population decreases due to increased illegal logging activities, especially in Gunung Palung National Park. This research aims to find out the density and spreading pattern of Shorea leprosula Miq. at Research Stasiun Cabang Panti, Gunung Palung National Park, West Kalimantan. The research was conducted from June to August 2020. The research method used is random sampling in 3 different locations, namely alluvial habitats, sandy rocks and freshwater swamps. Sampling using a squared method with a plot size of 20 x 20 m and made 10 plots on each habitat. The results showed that the density of S. leprosula is highest in freshwater swamp habitat of 170 individuals/Ha and the lowest in sandy rock habitat of 103 individuals/Ha. Spreading pattern S. leprosula is aggregate.